2011
DOI: 10.1136/bcr.11.2009.2455
|View full text |Cite
|
Sign up to set email alerts
|

Obscure-occult bleeding: resolution of unexplained chronic sideropenic anaemia by colonoscopic removal of a colonic leiomyoma

Abstract: BACKGROUNDSmooth muscle tumours of the gastrointestinal tract are uncommon, but those arising in the colon and rectum are rare and represent only 3% of all alimentary tract leiomyomas. 1 Several cases of endoscopic resection of colonic leiomyomas have been described. 2 3 Because conventional polypectomy of leiomyomas can result in perforation, the technique of submucosal injection polypectomy can be used to reduce the risk of this complication. We report a case of a woman affected by sigmoid leiomyoma in which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Large leiomyomas are also known to cause compressive and obstructive symptoms based on location. Bleeding from leiomyoma can vary from being detected on occult blood testing [8, 9] to more overt bleeding. Massive blood loss needing transfusion, perforation, obstruction, intussusception [10] and hemoperitoneum [11] are among the few complications described which generally require surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large leiomyomas are also known to cause compressive and obstructive symptoms based on location. Bleeding from leiomyoma can vary from being detected on occult blood testing [8, 9] to more overt bleeding. Massive blood loss needing transfusion, perforation, obstruction, intussusception [10] and hemoperitoneum [11] are among the few complications described which generally require surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic snare cauterization with or without saline lift has been described in literature especially for tumors involving the left colon [9, 12]. This partly could parallel the higher incidence of these tumors in left colon.…”
Section: Discussionmentioning
confidence: 99%
“…4,[11][12][13] Rarely, small leiomyomas less than 1 cm were reported to cause iron deficiency anemia, which was corrected after endoscopic resection. 10 Most polypoid leiomyomas of the colon and rectum presented endoscopically as small sessile polyps, with the exception of five pedunculated polyps. Although leiomyomas usually appear as a glistening, smooth, round sessile polyp on colonoscopy, they are occasionally indistinguishable from hyperplastic or adenomatous polyps.…”
Section: In a Large Series Involving Two Referral Centers In The Unitedmentioning
confidence: 97%
“…3 However, several case reports have shown that endoscopic resection of small polypoid leimyomas is feasible. 2,[4][5][6][7][8][9][10][11][12][13] Since screening colonoscopy for colorectal cancers became widely available, the detection of small polypoid leiomyomas by colonoscopy has increased. 14 In the present study, we evaluated clinicopatho-logical characteristics of colorectal polypoid leiomyomas and the efficacy and outcome of endoscopic removal of these lesions.…”
Section: Introductionmentioning
confidence: 99%